Genomics of Population Differentiation in Humpback Dolphins, Sousa spp. in the Indo-Pacific Ocean. (2nd December 2020) - Amaral, Ana R; Chanfana, Cátia; Smith, Brian D; Mansur, Rubaiyat; Collins, Tim; Baldwin, Robert; Minton, Gianna; Parra, Guido J; Krützen, Michael; Jefferson, Thomas A; Karczmarski, Leszek; Guissamulo, Almeida; et al.
Abstract: Speciation is a fundamental process in evolution and crucial to the formation of biodiversity. It is a continuous and complex process, which can involve multiple interacting barriers leading to heterogeneous genomic landscapes with various peaks of divergence among populations. In this study, we used a population genomics approach to gain insights on the speciation process and to understand the population structure within the genus Sousa across its distribution in the Indo-Pacific region. We found 5 distinct clusters, corresponding to S. plumbea along the eastern African coast and the Arabian Sea, the Bangladesh population, S. chinensis off Thailand and S. sahulensis off Australian waters. We suggest that the high level of differentiation found, even across geographically close areas, is likely determined by different oceanographic features such as sea surface temperature and primary productivity.